A new prognostic model including immune biomarkers, genomic proliferation tumor markers (AURKA and MYBL2) and clinical-pathological features optimizes prognosis in neoadjuvant breast cancer patients - García-Torralba, Esmeralda; Navarro Manzano, Esther; Luengo-Gil, Gines; De la Morena Barrio, Pilar; Chaves Benito, Asunción; Pérez-Ramos, Miguel; Álvarez-Abril, Beatriz; Ivars Rubio, Alejandra; García-Garre, Elisa; Ayala de la Peña, Francisco; García-Martínez, Elena (Frontiers in Oncology, 2023)
Up to 30% of breast cancer (BC) patients treated with neoadjuvant chemotherapy (NCT) will relapse. Our objective was to analyse the predictive capacity of several markers associated with immune response and cell proliferation combined with clinical parameters. This was a single-centre, retrospective cohort study of BC patients treated with NCT (2001-2010), in whom pretreatment biomarkers were analysed: neutrophil-to-lymphocyte ratio (NLR) in peripheral blood, CD3+ tumour-infiltrating lymphocytes (TILs), and gene expression of AURKA, MYBL2 and MKI67 using qRT-PCR. A total of 121 patients were included. Median follow-up was 12 years. In a univariate analysis, NLR, TILs, AURKA, and MYBL2 showed prognostic value for overall survival. In multivariate analyses, including hormone receptor, HER2 status, and response to NCT, NLR (HR 1.23, 95% CI 1.01-1.75), TILs (HR 0.84, 95% CI 0.73-0.93), AURKA (HR 1.05, 95% CI 1.00-1.11) and MYBL2 (HR 1.19, 95% CI 1.05-1.35) remained as independent predictor variables. Consecutive addition of these biomarkers to a regression model progressively increased its discriminatory capacity for survival. Should independent cohort studies validate these findings, management of early BC patients may well be changed.